Cultural Schemata and Linguistic Relativity: How Language Shapes Perception Across Diverse Communities - Muhammad Nur Iman; Nurasia Natsir; Aisyah Aulia Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study investigates the interplay between linguistic relativity and cultural schemata, examining how language encodes culturally salient concepts and shapes cognitive frameworks across diverse communities. Through ethnographic and psycholinguistic approaches, the study collects data from 12 different language communities with varied cultural backgrounds. Cross-linguistic and cross-cultural analyses reveal significant correlations between linguistic structures—such as grammatical categories, lexical distinctions, and metaphorical expressions—and culturally specific schemata in spatial, temporal, and social domains. Perception and cognitive reasoning experiments were conducted with 450 participants to test linguistic relativity hypotheses in cultural contexts. Quantitative and qualitative findings demonstrate that linguistic patterns both reflect and reinforce cultural norms, influencing perception and cognitive strategies. Analysis of cultural text corpora shows how linguistic categories serve as vehicles for internalizing cultural values and worldviews. Specifically, the study finds systematic variations in spatial information processing, time conceptualization, and social event interpretation that correlate with language features of respective communities. These results underscore the co-constitutive relationship between language and culture in shaping human thought, providing important implications for cross-cultural education, intercultural communication, and cognitive theory.